Louisiana Wild : The Protected and Restored Lands of The Nature Conservancy - Lockwood, C. C., 1949- (Book collections on Project MUSE., 2015)
"Baton Rouge- For nearly thirty years, The Nature Conservancy in Louisiana has served as a steward of the state's ecological riches, protecting and maintaining more than 285,000 acres of the state's land. Now, for the first time, readers can observe the vast array of flora and fauna found in these complex habitats in Louisiana Wild, with the photography of C. C. Lockwood. The scenic images that Louisiana brings to mind-moss-draped cypress, lush marshlands, alligators gliding through bayous, herons coasting across an open sky-all spring from one of the most diverse and productive ecosystems on the continent. This varied and inviting landscape gives rise to one of the state's many monikers, 'Sportsman's Paradise, which rings true whether you are boating on picturesque Lake Martin or bird-watching among the ancient live oaks of Lafitte Woods. From the precious maritime forests of Grand Isle to the steep contours of Tunica Hills, Louisiana's wild outdoors defines each region's sense of place and value. After trekking and canoeing through more than sixty properties managed by The Nature Conservancy, photographer C. C. Lockwood presents a vivid photo narrative that journeys from the little-known Copenhagen Hills, a prairie habitat with the largest variety of woody plants in Louisiana; to the swampland lake of Cypress Island, with its massive rookery of roseate spoonbills and great egrets; to over a dozen other sites that showcase Louisiana's distinct environs. With 220 color images, Louisiana Wild pays homage to the immeasurable impact of The Nature Conservancy's efforts and will delight anyone who calls Louisiana home" -- Provided by publisher.